The Significance Of Maternal Total Serum Homocysteine Level In Iraqi Mothers Who Had Previous Babies With Neural Tube Defects - Sadik, Bassam M.; AL-Taha, Salma A. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: Neural tube defects (NTDs) are said to be inherited in a multifactorial fashion, i.e. genetic-environmental interaction. Maternal nutritional deficiencies had long been reported to cause NTDs, especially folate deficiency during early pregnancy. More attention had been paid to the exact mechanism by which this deficiency state causes these defects in the developing embryo. The most significant of all researches was that connecting reduced folate and increased homocysteine level in maternal serum on one hand and the risk of developing a NTD baby on the other hand. Objectives : to determine the significance of homocysteine level in Iraqi mothers who gave birth to babies with NTDs as compared to normal controls. Patients, Materials and Methods: Fifty Iraqi women having babies born with NTDS, referred to the genetic clinic in Baghdad Teaching Hospital, were included in this study (the study group) as well as 37 healthy women having normal children (the control group). This study was conducted from November, 2002 till October, 2003. Analysis of total serum homocysteine level for all women was done using a computerized HPLC system. Results : the age of women in both groups was comparable (mean+SD in the study group was 26.2+5.14 years vs. 26.3+4.57 years in the controls). Among the study group, 4 (8%) had normal tHcy level; 44 (88%) had mildly elevated level, and only 2 (4%) had moderately elevated tHcy level, while all (100%) women in the control group had their tHcy level within normal level. This difference was statistically highly significant (p<0.001). Conclusions : Women become at an increased risk of delivering a baby with NTD when having an elevated tHcy level in their sera, and that tHcy level is an important marker in maternal serum that is associated significantly with pregnancy outcome.